Multiple perspectives on the concept of conditional probability - Manfred Borovcnik (Avances de Investigación en Educación Matemática)
Conditional probability is a key to the subjectivist theory of probability; however, it plays a subsidiary role in the usual conception of probability where its counterpart, namely independence is of basic importance. The paper investigates these concepts from various perspectives in order to shed light on their multi-faceted character. We will include the mathematical, philosophical, and educational